The Influence of Leadership and Motivation on the Performance of an Educational Institution: A Case Study - Ansori , Putra Budi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2021)
This study aims to determine the effect of leadership and work motivation on teacher performance in educational institutions. This research is quantitative research. The sample in this study were all teachers totaling 49 teachers. The research data used SPSS version 23. It was found that the F count was 22,052 > F table 3,20 so that simultaneously the variables of leadership and work motivation had a significant effect on teacher performance. the contribution of the influence of competence and work environment on teacher performance is 47.3%, while 52.7% is influenced by other factors that are not cultivated in this study.